2005
DOI: 10.1007/s11060-005-7409-5
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide after Radiotherapy for Newly Diagnosed High-grade Glioma and Unfavorable Low-grade Glioma in Children

Abstract: Chemotherapy is commonly used in the treatment of children with high-grade glioma, although its usefulness is uncertain. We conducted a multi-institutional study to evaluate the efficacy of temozolomide given after radiotherapy in children with newly diagnosed high-grade glioma and unfavorable low-grade glioma (gliomatosis cerebri or bithalamic involvement). Optional window therapy of intravenous irinotecan (10 doses of 20 mg/m2 per cycle x 2) was given over 6 weeks. The 5-day schedule of temozolomide (200 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 23 publications
1
47
0
2
Order By: Relevance
“…They reported that the 3-year EFS (eventfree survival) rate for GBM was 7% ± 4% in the children's oncology group study ACNS0126 compared with 15% ± 5% in the Children's Oncology Group study CCG-945. These results that temozolomide had no superiority to conventional treatments were reported as well in another study (7).…”
supporting
confidence: 69%
“…They reported that the 3-year EFS (eventfree survival) rate for GBM was 7% ± 4% in the children's oncology group study ACNS0126 compared with 15% ± 5% in the Children's Oncology Group study CCG-945. These results that temozolomide had no superiority to conventional treatments were reported as well in another study (7).…”
supporting
confidence: 69%
“…While initial trials by the CCG demonstrated improvements in PFS in patients treated with a combination of chemotherapy and radiation after resection, later trials were unable to replicate the initial findings [2,11,15]. Lack of new chemo-therapeutic combinations in the immediate postresection stage has kept the 5-year overall survival from high grade astrocytomas between 10-20% [1,3,16].…”
Section: Discussionmentioning
confidence: 99%
“…Initial trials by the Children's Cancer Group (CCG) in children with HGG treated with post-radiation chemotherapy (vincristine, lomustine and predinose) had an improved progression free survival (PFS) of 46% compared to 26% of those treated with radiation alone [15].Despite these initial findings, successive chemotherapeutic trials were unable to significantly improve outcomes [3,11]. Promising data has been published in adult patients with HGG treated with the methylating agent Temozolamide when administered with concurrent radiation therapy, suggesting a role for adjuvant chemotherapy in pediatric patients as well although subsequent trials have been slow to demonstrate similar improvement [1]. Recent trials in adults with recurrent glioblastoma multiforme have shown that the combination of Bevacixumab and Irinotecan have improved 6 month PFS was 46% and overall survival (OS) at 6 months of 77% [19].…”
Section: Introductionmentioning
confidence: 99%
“…[17] Erişkin GBM'li hastalarda Temozolomide'nin (TMZ) etkinliği gösterildikten sonra, birçok pediatrik çalışma bu tedavi protokolünü denemiş ancak benzer yaşam sürelerini gösterememiştir. [18][19][20] St Jude Çocuk Hastanesi'nde (SJHG98 study) yapılan çalışmada RT sırasında ve sonrasında TMZ verilen 31 yeni tanılı YDG'lu çocukta (GBM=15; AA=10; diğer YDG=4), 2 yıllık OS ve yaşam sü-resi sırasıyla %11±%5 ve %21 ±%7 olarak sonuç-lanmıştır. [19] COG'nin yeni tanılı YDG'lu hastalarda yaptğı en kapsamlı çalışmada (ACNS0126 çalışması), 99 hastaya (55 GBM, 31 AA ve 4 diğer YDG), RT (54Gy+boost 5.4 Gy) sırasında TMZ (90 mg/m 2 /g 42 gün) ve 4 hf dinlenme sonrasında TMZ 200 mg/m 2 /g x 5 g 28 g bir x 10 kür uygulanmıştır.…”
Section: Yüksek Dereceli Gliom Tedavisiunclassified
“…[18][19][20] St Jude Çocuk Hastanesi'nde (SJHG98 study) yapılan çalışmada RT sırasında ve sonrasında TMZ verilen 31 yeni tanılı YDG'lu çocukta (GBM=15; AA=10; diğer YDG=4), 2 yıllık OS ve yaşam sü-resi sırasıyla %11±%5 ve %21 ±%7 olarak sonuç-lanmıştır. [19] COG'nin yeni tanılı YDG'lu hastalarda yaptğı en kapsamlı çalışmada (ACNS0126 çalışması), 99 hastaya (55 GBM, 31 AA ve 4 diğer YDG), RT (54Gy+boost 5.4 Gy) sırasında TMZ (90 mg/m 2 /g 42 gün) ve 4 hf dinlenme sonrasında TMZ 200 mg/m 2 /g x 5 g 28 g bir x 10 kür uygulanmıştır. [20] CCG-945 çalışmasıyla karşılaştırıldı-ğında üç yıllık OS ve yaşam süreleri bakımından aralarında hiçbir fark bulunamamıştır.…”
Section: Yüksek Dereceli Gliom Tedavisiunclassified